Descriptions of two new species of Rhopalovalva Kuznetzov, 1964 (Lepidoptera: Tortricidae) from China - Zhang, Aihuan; Bai, Xia; Li, Houhun (Zootaxa, 2017)
Two new species of Rhopalovalva Kuznetzov are described from China: R. macrocuculla Zhang and Li, sp. nov., and R. connata Zhang and Li, sp. nov. Photographs of the adults and genitalia are provided. We report the first occurrence of the absence of an uncus in the male genitalia of a Rhopalovalva species. A key to the Chinese species is provided based on the characters of the male genitalia. We also comment on the generic characters of Rhopalovalva.